Changes in Vitamin D Status in Overweight Middle-Aged Adults with or without Impaired Glucose Metabolism in Two Consecutive Nordic Summers - Petra Lundström; Kenneth Caidahl; Maria J. Eriksson; Tomas Fritz; Anna Krook; Juleen R. Zierath; Anette Rickenlund (Journal of Nutrition and Metabolism)
Background. Sun exposure is the main driver of vitamin D synthesis. High latitude, obesity, and type 2 diabetes mellitus (T2DM) are all risk factors for vitamin D deficiency. However, the seasonal variation in vitamin D concentrations (25[OH]D) in such populations before and after sun exposure during the summer is unknown. Therefore, we investigated 25[OH]D status before and after two consecutive summers in high latitude and its associations with body fat, sex, and glucose metabolism. Methods. 158 participants from Sweden (87 women, 71 men; mean age, 60 ± 5 y; body mass index ≥ 25 kg/m2) and 25[OH]D were measured and evaluated in relation to normal or impaired glucose tolerance, body composition, and dietary habits during summer season. Results. Eighty-four percent of the participants were categorized with low to deficient 25[OH]D values before summer (55.1 ± 21.7 nmol·L−1), with a significant increase after the summer season (66.3 ± 21.0 nmol·L−1; P<0.001). However, the values remained below the recommended range (76–250 nmol·L−1) in 66% of the participants. These findings were verified in a subgroup of the study population during the subsequent summer. Participants who reported use of vitamin D supplements had higher initial concentrations (64.2 ± 20.1 nmol·L−1) compared to nonusers (53.7 ± 21.7 nmol·L−1; P=0.04). Further, 25[OH]D values correlated negatively with fat mass (kg) prior to summer only in the female population (r=−0.29, P=0.008). Conclusions. In the present study, sun exposure had a beneficial but insufficient effect on 25[OH]D levels, and the same levels were documented in two consecutive summer seasons, confirming that vitamin D supplementation in both summer and winter should be considered in this population.